How can a foundation be outlined for a successful serious game to increase reading engagement - Thomas Bjørner; Mads Strømberg Petersen; Niklas Lee Skjold Hansen; Gustav Jakobsen; Daniel Hendriksen (Serious Games Society, 2023)
This study aims to support a mandatory reading of a novella for high school students by a serious game. The study includes 41 students. The first class is included in the experimental study, which uses a serious game to read the novella. The second class served as the control group and engaged only in analog reading. The evaluation is based on a questionnaire with reading, user, and narrative engagement items. Furthermore, the assessment consists of in-depth interviews with teachers and students. The findings positively affected students' engagement in the experimental group. Primarily focused attention and reward are higher in the experimental group. However, there was no difference in the narrative engagement between the two groups, indicating that the story (digital or not) is well explained. The qualitative findings revealed positive comments, especially for the reading engagement and the story world. The novelty in this study is the outlined game design process, guided by elements in the foundation, game design, prototyping, and implementation. For the game design, we outlined how to transform the principles from Sweetser and Wyeth to applied design implementations. An important aspect was to illustrate the protagonist with schizophrenia.